The Alfred Hitchcock encyclopedia - Whitty, Stephen, 1959- (Lanham, Maryland : Rowman & Littlefield, 2016)
"Film critic Stephen Whitty provides a detailed overview of the director's work. This reference volume features in-depth critical entries on each of his major films as well as biographical essays on his most frequent collaborators and discussions of significant themes in his work. For this book, Whitty draws on primary-source materials such as interviews he conducted with associates of the director$1 (Bincluding screenwriter Jay Presson Allen (Marnie), actresses Eva Marie Saint (North by Northwest) and Kim Novak (Vertigo), actor Farley Granger (Strangers on a Train), actor and producer Norman Lloyd (Saboteur), and Hitchcock$1 (Bs daughter Patricia (Stage Fright; Psycho)$1 (Bamong others."--s
Includes bibliographical references and index.
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Encyclopedias